Pendampingan Pembelajaran Mendalam Melalui Pembelajaran Sains dan Seni Pada Pos PAUD Cendekia Mandiri Tambakaji Kota Semarang - Rofian; Mudzanatun; Fine Reffiane; Yosi Gumala (BALE LITERASI, 2026)
This community service initiative was conducted to foster an understanding of deep learning within the context of early childhood education. Deep learning at the early childhood level is grounded in three core principles: mindful learning, meaningful learning, and enjoyable learning. The initiative employed a Participatory Action Research (PAR) approach, comprising demonstrations, mentoring, and discussions. The results indicate that both teachers and parents of early childhood students improved their skills and understanding regarding deep learning practices. Deep learning in early childhood settings can be implemented through hands-on science activities with students; such activities facilitate the development of awareness, the discovery of meaning in learning, and an enjoyable understanding of scientific concepts. Integrating the arts into instruction fosters